The Impact of a Negative Labor Demand Shock On Fertility - Evidence From the Fall of the Berlin Wall - Hannah Liepmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
How does a negative labor demand shock impact fertility? I analyze this question in the context of the East German fertility decline after the fall of the Berlin Wall in 1989. I exploit differential pressure for restructuring across East German industries which led to unexpected, exogenous, and permanent changes to labor demand. I find that throughout the 1990s, women more severely impacted by the demand shock had relatively more children than their less-severely-impacted counterparts. Thus, the demand shock did not only depress the aggregate fertility level but also changed the composition of mothers. My paper shows that these two effects do not necessarily operate in the same direction.
Keywords: J13; J23; P36; 330; fertility; labor demand shock; industrial restructuring; east germany